Báo cáo kết quả công tác năm 2018 và dự kiến chương trình công tác năm 2019 của Ủy ban Pháp luật - Ủy ban Pháp luật (2018)
Báo cáo kết quả công tác năm 2018 và dự kiến chương trình công tác năm 2019 của Ủy ban Pháp luật.